STUDY OF THE CYTOLOGICAL AND MICRO-MORPHOLOGICAL CHARACTERISTICS OF SOME SPECIES OF THE GENUS EUPHORBIA L.BELONG TO EUPHORBIACEAE FAMILY , USING ELECTRON MICROSCOPE IN IRAQ - & et al., Sulaiman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate micro-morphological and cytological characteristics for sex species of Euphorbiaceae family in Baghdad during the two growing seasons 2018-2019 . The species are: Euphorbia granulate Forssk.,E.helioscopia L.,E. hirta L.,E. hypericifolia L., E. milli Des Moul .,E. puplus L. Which involved with morphological characters of pollen grains and seeds, as well the chromosomes number, and the study managed to count chromosome number for the above species sequentially:-n=11, n=21, n=9, n=16, n=14,18, n=7,8. The morphological characters of pollen grains surface has been studied by using scanning electron microscope (SEM), shape and size, polar and equatorial axes, spines length, dimensions of ora and colpi, and the ornamentations on pollen surface, and it has been observed that all the species are tri-zono-colporate, spinulose and spinate (echinated), and spinolophate fruite, and importance of the pollen grains in taxonomy. The study includes morphological characteristics of seeds by using (SEM) In terms of size, shape, color, and appearance of the seed surface(configuration). It has been shown that the seeds are significantly different from species to another. Species help to isolate and classify, and through relying on these characteristics, classification limits could be set, whether at the level of species or genus within each family.